In the name of ‘local sovereignty’ : peace from below through a leadership lens. A lesson from Côte d’Ivoire - Olonisakin, Funmi (University of Pretoria, 2025)
Thesis (PhD (Leadership and Security Studies))--University of Pretoria, 2023.